ACTIVATION OF PROVERBS AND SAYINGS OF THE RUSSIAN LANGUAGE WHEN STUDYING A NEW TOPIC - Xoshmuratova I. P. (Zeta Repository, 2023)
This paper discusses the activation of proverbs and sayings of the Russian language when studying a new topic. The role of proverbs and sayings in the formation of language competence and expansion of vocabulary is described. Particular attention is paid to the methods of activating proverbs and sayings, such as using context, game methods, creating associations, etc. Examples of the use of proverbs and sayings in various situations are given, which helps students to better understand and remember a new topic.